Mixed Effects of Marketing with Approach of Information Technology for Promotion of Customer's Loyalty in Hamadan Province Clubs - Ali Akbar Zohrevand (Journal of Global Pharma Technology, 2017)
The present study is Descriptive method type study from its application essence and in consideration to its objective, that has been conducted in the form of survey research. Statistical population is all the users of sports gymnasiums in Hamadan province that according to report from sports insurance control is reported to be 1000.statisticalsample was predicted to be 382 based on Morgan table easement tool includes ( consists of) mixed local marketing glue stingier (1389) and technical information Questionnaire (1395) .validity and reliability was obtained to be 0.80 for mix marketing element and 0.91 for technical information Questionnaire respectively by using Cranach Alpha. To analyze the data’s, discretional and interferential. Statistics such as Kolmogorov - Simonov test (test k-s), one sample t test, and freedman test was used. the results of this study showed that, there is a significant difference between the observed and imaginary average’s in mixed marketing elements ( t= 29/12 , p<0/001) .in the other word , situation of mixed marketing elements in sample study is little bet term than assumed or imaginary elements. Freedman test results showed that, the highest ranking average is for employee’s elements (4.46) and the lowest ranking is for product (2.72). It is recommended that all of employees or staff in sport clubs achieve the required or necessary skills. In using the internet, and also know the applied software packages which are related to their work area and have a special skills in utilizing then.Keywords: mixed marketing, Information technology, Customer’s loyalty. Clubs in Hamadan province.